Agronomic Response of Cicer Arietinum L. Varieties in Low Fertility - Saez-Tonacca, L (UNIV SANTIAGO DE CHILE, 2022)
The prices of the foods and agricultural inputs increase in the world, for what Cuba de-velops strategies that allow the production of grains like in chickpea (Cicer arietinum L.) in agroecosystem of low fertility. For it is indispensable to know the agronomic answer of the varieties of the vegetable species in soils with these characteristics. In this study the chic-kpea varieties National-24, National-29, National-30, National-6 and JP-94 was sowed in a soil with low values of organic matter and means values of phosphorus and potassium. Under these conditions was better the variety National 29 over the rest of them because presenting higher number and weight fresh of nodule, longitude of the root, wide of the glass, number of sheaths for plant, weight of 100 seeds and yield for plant. The results allow intending this to cultivate to sow in Cuba in agroecosystem with the same characteristic and to have good yields.